REGENERATIVE BRAKING MONITORING SYSTEM OF ELECTRIC VEHICLE - Jusuf Abimas Pratama; Miftahul Anwar; Sifaus Wulaning Arsri; Ferdiansyah Ashil Farisi; Muhammad Nizam (Journal of Electrical, Electronic, Information, and Communication Technology, 2019)
Electric vehicles is in rapid development. The energy commonly used as a driving force for electric vehicles comes from batteries. The development of electric vehicle technology is currently concentrated on efforts to charge the battery used by utilizing the power wasted when braking electrically. The gearbox and final drive are installed as a mechanical transmission system for electric vehicles to increase the torque of the BLDC motor as the main driving force of the vehicle. The regenerative process occurs when the Kelly-KBL motor controller electric braking feature is activated. For this reason, Arduino Mega and LabVIEW software are used to observe the current and voltage of lead acid batteries with voltage 48 V and capacity 225 Ah (C20). In addition, a 2 kW BLDC motor RPM was also observed in the electric braking monitoring system. From the results of monitoring and data collection, the vehicle traveled a distance of 36.06 m in 68 s time intervals with an average speed of 16.8 m / s. The average torque value when electric braking on a BLDC motor supplies 154 Nm, while the average torque of the vehicle is 996.99 Nm. The average regenerative power of the wheels is 17.07 kW, while the average mechanical power of the wheels is 13.67 kW. Coulometric state of charge (SOC) shows an increase in battery capacity of 4.27% and 99.97% voltage SOC at the beginning of the activation of the electric brake pedal. Maximum battery power movement when charging, 2.25 kW is caused by the activation of the electric brake pedal. Whereas when using a maximum of 1.52 kW. The application of electric braking has a power consumption efficiency of 0.042%. and charging power charging 18.97%.